Explanation:
=(5x+4)°
=(2x-2)°
=(4x-6)°
we know that,
=+
According to the question,
so,
=(4x-6)°=(4×12-6)°=(48-6)°=42°
Answer:
m<C = 42°
Given:
m<A = (2x - 2)°
m<C = (4x - 6)°
m<DBC = (5x + 4)°
Thus:
m<DBC = m<A + m<C (exterior angle theorem of a triangle)
(5x + 4)° = (2x - 2)° + (4x - 6)°
Solve for x
5x + 4 = 2x - 2 + 4x - 6
Collect like terms
5x + 4 = 6x - 8
5x - 6x = -4 - 8
-x = -12
Divide both sides by -1
x = 12
✔️m<C = (4x - 6)°
Plug in the value of x
m<C = 4(12) - 6 = 48 - 6
5.6m questions
7.3m answers